Entre el ser y el parecer: La dualidad de los personajes dramáticos en Saverio el cruel - Sanhueza, María Teresa (Latin American Theatre Review, 2001)
This study suggests that Roberto Arlt’s play Saverio el cruel (1936) portrays characters that show interplay between reality and fantasy. Arlt uses methatheatre to present a picture of a "reality" subverted by another reality, which, while being the product of imagination, comes to be just as real to the characters experiencing it as the reality within which it was created. This "duality of planes" is the result of the relationships between the literary conventions of "teatro dentro del teatro" and Arlt and the world that surrounds him. Thus, the "performance within the performance" serves as a mechanism to show the playwright’s commentaries on three important issues of national and world interest: the dialectic relationship between reality and fiction, the social differences within Argentina’s society, and his own view of dictatorships and power. (MTS)